Health-related quality of life in breast cancer patients in Asia: A meta-analysis and systematic review - Chen, Xinyu; Wu, Chenxi; Bai, Dingxi; Gao, Jing; Hou, Chaoming; Chen, Tingting; Zhang, Lulu; Luo, Huan (Frontiers in Oncology, 2022)
Objectives The primary purposes of this meta-analysis and systematic review were to evaluate the health-related quality of life (HRQoL) of Asian breast cancer (BC) patients to understand their holistic HRQoL level and provide medical and nursing recommendations to improve and preserve their quality of life. Methods A comprehensive literature search was conducted to find cross-sectional studies published in Chinese and English concerning HRQoL in BC patients from the inceptions of databases to 14 March 2022. The databases consulted were PubMed, Web of Science, Embase, Cochrane, PsyclNFO, CINAHL, and CNKI. Literature screening, data extraction, risk bias assessment, and data synthesis were independently carried out by two researchers. The Endnote X9 and Stata 15.0 software programs were used during the meta-analysis process. Results Out of the 8,563 studies identified, 23 cross-sectional studies involving 3,839 Asian BC patients were included in this meta-analysis. Two tools, namely, European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire C30 (EORTC QLQ-C30) and Quality of Life Questionnaire Breast Cancer module 23 (EORTC QLQ-BR23)—were used to evaluate the HRQoL of BC patients in Asia. The pooled mean of the global health status of Asian BC patients was 58.34 (95% confidence interval [CI]: 53.66–63.02). According to functional subscales of EORTC QLQ-C30 and EORTC QLQ-BR23, Asian BC patients suffered from the worst emotional functioning (pooled mean=66.38; 95% CI: 59.66–73.11) and sexual enjoyment (pooled mean=49.31; 95% CI: 31.97–63.36). In addition, fatigue (pooled mean=42.17; 95% CI: 34.46–49.88) and being upset by hair loss (pooled mean=48.38; 95% CI: 36.64–60.12) were the most obvious symptoms that Asian BC patients experienced according to the meta-analysis results of the EORTC QLQ-C30 and EORTC QLQ-BR23 symptom subscales. Conclusion Asian BC patients experience a relatively low HRQoL due to the prominent decline in their body functions, as well as the unpleasant experiences caused by their symptoms. It is suggested that timely, appropriate, and targeted intervention should be provided in relation to the physical, psychological, and social aspects of Asian BC patients’ lives to enhance their ability to function, relieve them of adverse symptoms, and improve their overall HRQoL. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022321165.